Welfare consequences of selling public enterprises : an empirical analysis - Galal, Ahmed; Fadil, Abbas; Jones, Leroy; Tandon, Pankaj; Vogelsang, Ingo (Oxford ; New York : Published for the World Bank [by] Oxford University Press, 1994)
Featuring case studies from Chile, Malaysia, Mexico and the UK, this study examines the effects of public enterprise divestiture in economies where capitalism and socialism are combined.
"A World Bank book."
Includes bibliographical references (p. 591-601) and index.
osc 1/9/16
Loans
Keywords: Privatization; Government business enterprises